Japanese Language Rhetoric of the Japanese Education Students’ at the Speech Contest - Rike Febriyanti (Bina Nusantara University, 2019)
The research aimed to analyze the speech rhetoric quality of the students of Japanese Language Education, Brawijaya University using a descriptive qualitative design. The method applied a discourse analysis method written by Krippendoff which included coding, classification, interpretation, and evaluation. The object of this research was students’ speech for Japanese Speech Contest of UB 2018. The data were seven video recordings of seven speeches delivered by seven students who participated in this speech contest. It it concluded that the quality of the students’ speech is not satisfactory in the criteria of content and expression. The students also show weaknesses in pronunciation and grammar in their speech. This research indicates that when the students are allowed to be honest to express their mind freely in the Japanese language, the speech will reflect each student’s actual language mastery, because language teaching inside the classroom is the most dominant language exposure for the students, any advancement in Japanese language teaching will significantly uplift the quality ofthe speech.